(untitled) (Research, Society and Development, 2024)
The dental internship allows the student to develop and evaluate their acquired knowledge, through the practical demonstration of motor skills, dexterity and aptitude for working in the oral environment. The objective of this study was to evaluate the dental internship at the State University of Amazonas through qualitative and quantitative analysis of the procedures performed and to evaluate the impact that the COVID-19 pandemic had on it. Quantitative data on care and qualitative evaluation of procedures from the dentistry internship of the 9th period of graduation were collected, being carried out in two periods before the COVID-19 pandemic and two periods during the pandemic. The data underwent descriptive and statistical analysis, using the Kruskal-Wallis test, and if there was a statistical difference (p<0.05), the Student-Newman-Keuls test. Statistic difference was observed in the average number of procedures performed per period (p<0.05). During the period without the presence of COVID-19, in the first half of 2019, the average was 54.4 procedures and 39.8 in the second half. In periods pandemic, in the first half of 2020, the average was 4.1 procedures, increasing to 21.7 in the second half. This pattern was seen in the average number of patients treated, reflecting in a decrease in the number of treatments carried out. The procedures considered invalidated remained at low levels and the area of dentistry is the area with the highest demand for care. Concluded that COVID-19 had a major impact on dental education, resulting in lower utilization of undergraduate Dentistry internships.